Higher lactate production from glucose in cultured adipose nucleated stromal cells than for rat adipocytes - Floriana Rotondo; Ana-Cecilia Ho-Palma; María del Mar Romero; Xavier Remesar; José Antonio Fernández-López; Marià Alemany (Adipocyte, 2019)
White adipose tissue (WAT) nucleated stromal cells (NSC) play important roles in regulation, defense, regeneration and metabolic control. In WAT sites, the proportions and functions of NSC change under diverse physiological or pathologic conditions. We had previously observed the massive anaerobic wasting of glucose to lactate and glycerol in rat epididymal adipocytes. To test site variability, and whether the adipocyte extensive anaerobic metabolism of glucose was found in NSC, we analyzed, in parallel, subcutaneous, mesenteric and epididymal WAT of male adult Wistar rats. Adipocytes and NSC fractions, were isolated, counted and incubated (as well as red blood cells: RBC) with glucose, and their ability to use glucose and produce lactate, glycerol, and free fatty acids was measured. Results were computed taking into account the number of cells present in WAT samples. Cell numbers were found in proportions close to 1:13:100 (respectively, for adipocytes, NSC and RBC) but their volumes followed a reversed pattern: 7,500:10:1. When counting only non-fat cell volumes, the ratios changed dramatically to 100:10:1. RBC contribution to lactate production was practically insignificant. In most samples, NSC produced more lactate than adipocytes did, but only adipocytes secreted glycerol (and fatty acids in smaller amounts). Glucose consumption was also highest in NSC, especially in mesenteric WAT. The heterogeneous NSC showed a practically anaerobic metabolism (like that already observed in adipocytes). Thus, NSC quantitative production of lactate markedly contributed (i.e. more than adipocytes) to WAT global use (wasting) of glucose. We also confirmed that glucose-derived glycerol is exclusively produced by adipocytes.